PENGARUH DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. PERKEBUNAN NUSANTARA V PKS (Pabrik Kelapa Sawit) SEI ROKAN (KASUS KARYAWAN BAGIAN PENGOLAHAN) - Martha Ulina Hutagalung; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Discipline of work is undertaken efforts to create a working environment that isorderly, efficient and successful through proper regulatory system. The disciplinaryprocedures are included in the work in this study is about, time discipline, discipline anddiscipline task behavior.Labor productivity is a mental attitude that always mempunai view that quality of lifeshould be better today than yesterday and tomorrow should be better than today. Laborproductivity assessed in this study is about, the quantity of work, quality of work andtimeliness of work.PT. Nusantara Plantation V MCC Sei Rokan is a company engaged in the business ofplantation, processing and marketing of farm products, namely palm oil (CPO) and palmkernel (Karnel). Processing part is the most important part of business units MCC (mills) isbecause the processing section which produce palm oil products and Karnel, and in thissection is required of employees who actually have a high hard work to get results that meetthe CPO and Karnel targets the company.Based on the analysis of this study showed that the discipline of work has a positiveimpact on employee productivity processing part of PT. Nusantara Plantation V MCC SeiRokan. It can be seen from the analysis of known data from the t (30.401)> t table (2.600)and sig (0,000) <0.05. Then the hypothesis is no influence on the productivity of labordiscipline is acceptable.Keywords: Work Discipline, Work Productivity, Discipline and Productivity